Enhancement of transgene expression by mild hypothermia is promoter dependent in hek293 cells - Jang, Min Ho; Min, Honggi; Lee, Jae Seong (Life, 2021)
Mild hypothermia has been widely used to enhance transgene expression and improve the cellular productivity of mammalian cells. This study investigated mild hypothermia-responsive exogenous promoters in human embryonic kidney 293 (HEK293) cells using site-specific integration of various promoter sequences, including CMV, EF1α, SV40, and TK promoters, into the well-known genomic safe harbor site, AAVS1. EGFP expression driven by the CMV promoter increased up to 1.5-fold at 32◦C versus 37◦C under stable expression, while others showed no hypothermic response. Integration of short CMV variants revealed that the CMV-enhancer region is responsible for the positive hypothermic response. CMV-enhancer-specific transcription factors (TFs) were then predicted through in silico analysis and RNA-sequencing analysis, resulting in the selection of one TF, NKX3-1. At 37◦C, overexpression of NKX3-1 in recombinant HEK293 cells expressing EGFP through the CMV promoter (CMV-EGFP) increased EGFP expression up to 1.6-fold, compared with that in CMV-EGFP, the expression level of which was comparable to that of CMV-EGFP at 32◦C. Taken together, this work demonstrates promoter-dependent hypothermia responses in HEK293 cells and emphasizes interactions between endogenous TFs and promoter sequences.
Keywords: CMV promoter; HEK293 cells; Hypothermia; Low culture temperature; Transcription factor